Keyakinan Epistemik Mahasiswa PGSD tentang Pembelajaran IPS di Sekolah Dasar - Karimatus Saidah (Peneliti.net, 2023)
Epistemic belief is one's belief in the nature of knowledge and the nature of knowing. Epistemic beliefs can influence a prospective teacher's decision in determining learning strategies and models later. This study aims to reveal the epistemic beliefs of PGSD students. The research method used is a qualitative descriptive method. The results of the study show that students show consistent agreement with regard to the dimensions of achieving truth in learning social studies in elementary school where students assume that truth is something that can be achieved and the simplicity of knowledge where social studies knowledge in elementary school is an interrelated concept of on facts. On the other three dimensions related to certainty of knowledge, sources of knowledge and justification of student knowledge show inconsistent results